Text genetics in literary modernism and other essays - Gabler, Hans Walter, 1938- (Open Book Publishers, 2018)
"This collection of essays from world-renowned scholar Hans Walter Gabler contains writings from a decade and a half of retirement spent exploring textual criticism, genetic criticism, and literary criticism. In these sixteen stimulating contributions, he develops theories of textual criticism and editing that are inflected by our advance into the digital era; structurally analyses arts of composition in literature and music; and traces the cultural implications discernible in book design, and in the canonisation of works of literature and their authors. Distinctive and ambitious, these essays move beyond the concerns of the community of critics and scholars. Gabler responds innovatively to the issues involved and often endeavours to re-think their urgencies by bringing together the orthodox tenets of different schools of textual criticism. He moves between a variety of topics, ranging from fresh genetic approaches to the work of James Joyce and Virginia Woolf, to significant contributions to the theorisation of scholarly editing in the digital age. Written in Gabler's fluent style, these rich and elegant compositions are essential reading for literary and textual critics, scholarly editors, readers of James Joyce, New Modernism specialists, and all those interested in textual scholarship and digital editing under the umbrella of Digital Humanities."--Publisher's website